MANAJEMEN BERBASIS SEKOLAH: PERUBAHAN SISTEM OFFLINE KE ONLINE PADA MASA COVID-19 - Ninda Shavera Vista Happy Yana; Enung Hasanah; Windy Wirdo Ningrum; Asy Syifa Dhewi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The existence of the Covid-19 disaster has changed most of the executive orders in schools. Changes in Organizational Behavior in the form of new policies in the field of education to overcome the Covid-19 pandemic have become a standard solution that occurs almost throughout schools. This study explores changes in education management in schools during the covid-19 period. This study uses qualitative research methods. The results showed that the change from an offline system to online learning had triggered the emergence of new things in the field of education management, namely: 1) the form of learning from offline changed to distance learning; 2) accelerated utilization of high technology; and 3) analog learning model became multi-source. In implementing school management policies during the transition period, support from various parties is needed so that everything runs as planned by the school management.